2007
DOI: 10.1200/jco.2006.09.3534
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression Patterns and Interaction Networks in BCR-ABL–Positive and –Negative Adult Acute Lymphoblastic Leukemias

Abstract: We identified prominent molecular features of BCR-ABL-positive adult ALL, which may be useful for developing novel therapeutic targets and prognostic markers in this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 46 publications
5
73
0
3
Order By: Relevance
“…6 Genome-wide profiling, along with association studies and immunohistochemistry, demonstrated that XBP1 expression was induced in a variety of primary cancers or cancer cell lines including hematological malignancies such as multiple myeloma and acute lymphoblastic leukemias, [7][8][9] as well as breast cancers, 10,11 hepatocellular carcinoma, 12,13 pancreatic adenocarcinomas, 14,15 and colon cancer. 16,17 It has been demonstrated that XBP1 is activated in primary mammary tumors, and that its expression correlates with enhanced tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…6 Genome-wide profiling, along with association studies and immunohistochemistry, demonstrated that XBP1 expression was induced in a variety of primary cancers or cancer cell lines including hematological malignancies such as multiple myeloma and acute lymphoblastic leukemias, [7][8][9] as well as breast cancers, 10,11 hepatocellular carcinoma, 12,13 pancreatic adenocarcinomas, 14,15 and colon cancer. 16,17 It has been demonstrated that XBP1 is activated in primary mammary tumors, and that its expression correlates with enhanced tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…They have been produced for the study of the gene expression profiles of 54 specimens of acute lymphoblastic leukemia. The specimens span 37 positive and 17 negative to BCR-ABL [10], which is a fusion gene product resulting from translocation between the 9th and the 22th chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…64 Insulin receptor substrate 1 is a docking protein for the insulin-like growth factor type 1 receptor and the insulin receptor, which sends mitogenic and antiapoptotic signals as part of an oncogenic pathway, and is differentially expressed in B cells and myeloid leukemia cells. 65 Furthermore, miR-145 participates in p53-dependent regulation of the oncogene c-Myc, as expression of this miRNA is directly induced at the transcriptional level by p53 and directly repressed at the posttranscriptional level by c-Myc, consequently inhibiting tumor cell growth. 66 This specific function may explain why B cells in CLL can acquire additional growth advantages by loss of expression of this miRNA.…”
Section: Self-sufficiency In Growth Signalsmentioning
confidence: 99%